Does a waist-worn accelerometer capture intra- and inter-person variation in walking behavior among persons with multiple sclerosis? - Motl, Robert W. (2010)
The valid application of accelerometry and interpretation of its output (i.e., counts per unit time) for the measurement of walking behavior in persons with multiple sclerosis (MS) rests upon multiple untested assumptions. This study tested the assumption that a waist-worn accelerometer should capture the intra- and inter-person variation in walking behavior. Twenty-four participants with a neurologist-confirmed diagnosis of MS and who were ambulatory with minimal assistance undertook three 6-min periods of over-ground walking that involved comfortable (CWS) and then slower (SWS) and faster (FWS) walking speeds while wearing ActiGraph, model 7164, accelerometers around the waist and ankle. The experimental manipulation of walking was successful such that the CWS was 76.7 ± 13.0 m/min (range = 55.6–105.14), whereas the SWS and FWS were 64.3 ± 12.3 m/min (range = 44.5–90.1) and 89.1 ± 13.8 m/min (range = 60.9–116.4), respectively. Movement counts from the waist and ankle-worn accelerometer were strongly associated with the manipulation of speed, but the association was stronger for the waist than ankle based on both eta-squared estimates (η(2) values = .78 and .46) and the average squared multiple correlations from individual regression analyses (R(2) values = .97 ± .04 and .88 ± .21). The bivariate correlation between movement counts from the waist-worn accelerometer and speed of walking (r = .823, p = .001) was large in magnitude and significantly different (z = 3.22, p = .001) from that between movement counts from the ankle-worn unit and walking speed (r = .549, p = .001). This study provides novel evidence that an accelerometer worn around the waist captures intra- and inter-person variation in over-ground walking behavior in those with MS.